2021
DOI: 10.15252/embr.202051136
|View full text |Cite
|
Sign up to set email alerts
|

BioID reveals an ATG9A interaction with ATG13‐ATG101 in the degradation of p62/SQSTM1‐ubiquitin clusters

Abstract: ATG9A, the only multi-pass transmembrane protein among core ATG proteins, is an essential regulator of autophagy, yet its regulatory mechanisms and network of interactions are poorly understood. Through quantitative BioID proteomics, we identify a network of ATG9A interactions that includes members of the ULK1 complex and regulators of membrane fusion and vesicle trafficking, including the TRAPP, EARP, GARP, exocyst, AP-1, and AP-4 complexes. These interactions mark pathways of ATG9A trafficking through ER, Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 87 publications
(112 reference statements)
8
35
0
Order By: Relevance
“…We next investigated the relation of ATG9A to SVs. As previously described 31, 32 , when expressed alone, ATG9A-EGFP was enriched in the Golgi complex, but also localized in scattered puncta throughout the cytoplasm (Fig. 3a).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We next investigated the relation of ATG9A to SVs. As previously described 31, 32 , when expressed alone, ATG9A-EGFP was enriched in the Golgi complex, but also localized in scattered puncta throughout the cytoplasm (Fig. 3a).…”
Section: Resultssupporting
confidence: 80%
“…However, substantial differences between the two biotinylated proteomes were also detected. Consistent with previous studies, ATG9A samples were enriched in subunits of AP4 (an heterotetrameric complex responsible for the sorting of ATG9A at the TGN) 31,32,34 , in AP4 interactors (tepsin and rusc2) 32,34,35 , in subunits of the PIKfyve complex (a phosphoinositide metabolizing complex that that function at late endosomes/lysosomes) 36 as well as in the autophagy factors ULK1 and ATG13 37 (Fig. 5c).…”
Section: Distinct Features Of Synaptophysin Vesicles and Atg9a Vesicl...supporting
confidence: 91%
“…Removing the WF finger of ATG101 (WF to DD) had no effect on ATG9A binding. Our mutational analysis suggests that the hydrophobic groove drives ATG9A binding and explains the need for both ATG101 and ATG13 in binding ATG9A in vivo (Kannangara et al 2021).…”
Section: Resultsmentioning
confidence: 96%
“…The ATG9A, ATG13 and ATG101 form a multifunctional hub at an early stage of starvation-induced autophagy and mitophagy initiation (Dalle Pezze et al 2021; Karanasios et al 2016; Zachari et al 2019). A BioID mass spectroscopy approach revealed that ATG13:ATG101 can recruit ATG9A during p62-dependent autophagy, independent of FIP200 and ULK1 (Kannangara et al 2021). Deletion of ATG13 or ATG101 led to a mislocalization of ATG9A, leading in turn to an accumulation of p62 aggregates identical to the ATG9A KO phenotype (Kannangara et al 2021; Saitoh et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation